Bis‐Sulfone‐ and Bis‐Sulfoxide‐Spirobifluorenes: Polar Acceptor Hosts with Tunable Solubilities for Blue‐Phosphorescent Light‐Emitting Devices. Issue 11 (29th March 2016) - Ertl, Cathrin D.; Bolink, Henk J.; Housecroft, Catherine E.; Constable, Edwin C.; Ortí, Enrique; Junquera‐Hernández, José M.; Neuburger, Markus; Shavaleev, Nail M.; Nazeeruddin, Mohammad Khaja; Vonlanthen, David
Abstract: Bis‐sulfone‐ and bis‐sulfoxide‐spirobifluorenes are a promising class of high‐triplet‐energy electron‐acceptor hosts for blue phosphorescent light‐emitting devices. The molecular design and synthetic route are simple and facilitate tailoring of the solubilities of the host materials without lowering the high‐energy triplet state. The syntheses and characterization (including single‐crystal structures) of four electron‐accepting hosts are reported; the trend in their reduction potentials is consistent with the electron‐withdrawing nature of the sulfone or sulfoxide substituents. Emission maxima of 421–432 nm overlap with the MLCT absorption of the sky‐blue emitter bis(4, 6‐difluorophenyl‐pyridinato)(picolinato)iridium(III) (FIrpic), allowing effective energy transfer from the acceptor hosts to FIrpic. Theoretical calculations show that the introduction of sulfone groups leads to better electron acceptors compared to analogous phosphine oxide functionalized hosts and, at the same time, preserves the energy of the lowest‐lying triplet above that of the FIrpic emitter. The new hosts have been tested in phosphorescent light‐emitting electrochemical cells (LECs). Large effects of the various solubilizing moieties on the device performance are observed and discussed. Abstract : Bis‐sulfone‐ and bis‐sulfoxide‐spirobifluorenes are a promising class of high‐triplet‐energy electron‐acceptor‐hosts for blue phosphorescent light‐emitting devices. Using a simple synthetic route amenable to tailoring host solubility, we have generated and evaluated a series of polar acceptor hosts. The effects of solubilizing moieties on host light emission capabilities are discussed.